Socioeconomic inequalities in healthcare system efficiency in Japan during COVID-19 pandemic: an analysis of the moderating role of vaccination - Tang, Yin (Frontiers in Public Health, 2024)
In the context of the COVID-19 pandemic, limited research has focused on socioeconomic disparities in Local Healthcare System Efficiency (LHSE) among Japanese prefectures. This study seeks to investigate the moderating impact of vaccination on the relationship between LHSE and socioeconomic characteristics and endowments using the Seemingly Unrelated Estimation t-test. LHSE is assessed utilizing the Data Envelopment Analysis with Slack-Based Measure, drawing upon data from Japanese prefectures during waves 2 to 5 of the pandemic. The research findings suggest an overall reduction in LHSE disparities across various regions due to the utilization of vaccines. Particularly in areas with relatively insufficient bed resources, a significant improvement in LHSE was observed in most regions. However, there was no evidence supporting the role of vaccine deployment in mitigating socioeconomic inequalities in LHSE. Conversely, the utilization of vaccines showed a positive correlation between the improvement in LHSE and the proportion of elderly population in regions with sufficient bed resources. In regions facing bed shortages, the enhancement of LHSE became more reliant on reducing the occupancy rate of secured beds for severe cases. This outcome emphasizes the need for policymakers and implementers, in pursuit of improving LHSE, to prioritize the treatment of severe cases and ensure an effective supply of medical resources, particularly secured beds for severe cases.